Changing Land Use in Recent Decades and Its Impact on Plant Cover in Agricultural and Forest Landscapes in Poland - Bomanowska, Anna; Kiedrzyński, Marcin (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The objective of this paper is to present the effects of general changes in land use in recent decades on plant cover structure in Poland. The paper is focused on spontaneous processes that occur in agricultural and forest areas being no longer under human pressure. Studies carried out in different geobotanical regions of Poland demonstrated that the directions and range of dynamic changes in plant cover are similar across the country. The formation of secondary forest phytocenoses, on the lands delivered from human activity is a common ecological process observed today in the agricultural landscape. In the dynamics of forest vegetation the basic process is regeneration after ceased use, and the introduction of legal protection.